2020
DOI: 10.3390/ma13225078
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Viscoelasticity of Dental Soft Polymer Material Containing Citrate Ester-Based Plasticizers

Abstract: The aim of this study was to investigate the dynamic viscoelasticity of dental soft polymer material containing citrate ester-based plasticizers. Three kinds of citrate ester-based plasticizer (Citroflex® C-2: TEC, Citroflex® A-2: ATEC, and Citroflex® A-4: ATBC), with the combination of 5 wt% ethyl alcohol, were used as the liquid phase. The dynamic viscoelastic properties of nine ethyl methacrylate polymers: (A, B, C, D, E, F, G, H, and I) were immersed in 37 °C distilled water for 0, 1, 3, 7, 14 and 30 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, this problem can be solved by the addition of some additive's compounds such as citrate ester-based plasticizer. The citrate esterbased plasticizer has significant properties in improving the durability of dental soft polymer materials [16]. On the other hand, the acrylic soft liners were preferred as it makes the dentures less painful compared to the silicone based soft liners.…”
Section: Classifications Of Soft Tissue Linersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this problem can be solved by the addition of some additive's compounds such as citrate ester-based plasticizer. The citrate esterbased plasticizer has significant properties in improving the durability of dental soft polymer materials [16]. On the other hand, the acrylic soft liners were preferred as it makes the dentures less painful compared to the silicone based soft liners.…”
Section: Classifications Of Soft Tissue Linersmentioning
confidence: 99%
“…They proposed that the biomechanical theory of the conventional complete dentures is in need for a serious change of dynamic mechanical resistance between the denture base and the oral mucosa [28]. In another recent in vitro study, Hong et al, [16] suggested that the addition of citrate esterbased plasticizer can improve the viscoelastic properties and expand the sturdiness of soft liners. In addition, oral mucosa has demonstrated referent biopolymer viscoelastic mechanical property in vitro which is comparable to soft liners [16,29].…”
Section: Physical and Chemical Characteristics Of Soft Linersmentioning
confidence: 99%
“…Plasticizers provide softness or resilience to this type of material at body temperature. Plasticizers are soluble in oral fluids, and their gradual loss over time leads to hardening of the material in the patient’s mouth [ 17 ]. Given the proven toxicity of phthalates, the most commonly used plasticizers in dental acrylates, their replacement with citrates would significantly improve the biological value of dental acrylates.…”
Section: Composition Of Dental Acrylate Polymersmentioning
confidence: 99%
“…Moreover, TMA is also very commonly used to study the thermal expansion of polymer [16,17], inorganic non-metallic [18], and composite materials [19,20]. The DMA method has also been used to study the thermal expansion coefficient, but it is more complex than the TMA method due to its frequency effect [21]. In measuring viscoelasticity and related storage modulus loss modulus, the DMA method is highly effective [22].…”
Section: Introductionmentioning
confidence: 99%